A special adoption managed with a private agency for the pregnant women with Japanese regular prenatal care: A case report - Akazawa, Munetoshi; Hashimoto, Kazunori (Journal of Japan Society of Perinatal and Neonatal Medicine, 2020)
Traditionally, public agencies in Japan, called “child consultation centers”, and private agencies by nonprofit organization have been responsible for special adoption. On April 1, 2018, the "Act on the Protection of Children Related to Adoption Mediation by Private Agencies" was enforced, and all private agencies need permission from the governments. However, it cannot be said that the understanding of special adoption has spread in the clinical field of perinatal care, and there is also little information that can be accessed regarding private agencies. We reported a case of adjusting the special adoption with a private agency for a pregnant woman who had not received regular perinatal cares. A-37-year-old pregnant women（gravida: 4, para: 3）was admitted to our hospital under the diagnosis of acute pyelonephritis. The patient did not received prenatal checkup at all before the admission, thus, we diagnosed the pregnancy of 32-week-gestaion from the fetometry. After the discharge, she did not receive regular prenatal checkup. At the 37-week-gestation, we was able to contact with her, and she has admitted again, receiving the scheduled cesarean section. On the operative day, she claimed that adoption be adjusted with private agencies. We contacted the one of private agencies, and the patient had the interview with the members of the private agencies after the delivery. At the discharge, the baby transferred to the affiliated hospital of the private agencies. Two months after the birth, the baby was taken in by an adoptive parent.